2010
DOI: 10.1124/dmd.110.032995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatic Organic Anion-Transporting Polypeptide by RNA Interference in Sandwich-Cultured Human Hepatocytes: An In Vitro Model to Assess Transporter-Mediated Drug-Drug Interactions

Abstract: ABSTRACT:Organic anion-transporting polypeptides (OATPs), members of the SLCO/SLC21 family, mediate the transport of various endo-and xenobiotics. In human liver, OATP1B1, 1B3, and 2B1 are located at the basolateral membrane of hepatocytes and are involved in hepatic drug uptake and biliary elimination. Clinically significant drug-drug interactions (DDIs) mediated by hepatic OATPs have drawn great attention from clinical practitioners and researchers. However, there are considerable challenges to prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
(40 reference statements)
0
11
1
Order By: Relevance
“…In total, these results are consistent with those noted in a recent review, which indicates the hepatocyte culture model maintains cell integrity and viability (Swift et al, 2010) and suggests the increase in CYP1A2 activity is unlikely to be due to cellular stress generated during long culture periods. Although the mechanism underlying the increase in CYP1A2 activity was not defined in the present study, the findings conflict with a recent study that reports a substantial decrease in all P450 enzyme activity in 5-day SCHH (Liao et al, 2010). Because CYP1A2 is a highly inducible protein, we speculate that this discrepancy can potentially be attributed to the culture conditions, and further investigation is needed to elucidate the mechanism of CYP1A2 modulation in SCHH.…”
Section: Kimoto Et Alcontrasting
confidence: 55%
“…In total, these results are consistent with those noted in a recent review, which indicates the hepatocyte culture model maintains cell integrity and viability (Swift et al, 2010) and suggests the increase in CYP1A2 activity is unlikely to be due to cellular stress generated during long culture periods. Although the mechanism underlying the increase in CYP1A2 activity was not defined in the present study, the findings conflict with a recent study that reports a substantial decrease in all P450 enzyme activity in 5-day SCHH (Liao et al, 2010). Because CYP1A2 is a highly inducible protein, we speculate that this discrepancy can potentially be attributed to the culture conditions, and further investigation is needed to elucidate the mechanism of CYP1A2 modulation in SCHH.…”
Section: Kimoto Et Alcontrasting
confidence: 55%
“…The importance of the OATP1B1 transporter in cerivastatin metabolism is highlighted in a recent publication showing that OATP1B1 inhibition by siRNA led to a 20–30% reduction in total uptake of cerivastatin into human hepatocytes, 50% reduction in formation of M-1 cerivastatin metabolite, and no change in M-23 formation [32]. Transporter– enzyme interplay is now well recognized as an important factor influencing drug metabolism [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that recent research findings have demonstrated that in addition to drug metabolizing enzyme activities, uptake and efflux transporters also play critical roles in the manifestation of adverse drug effects 10,45 . Human hepatocyte assays for the evaluation of uptake and efflux transporters have been established and are being applied towards drug development [46][47][48][49][50] . These transporter assays, when applied in conjunction with the assays described in this chapter, should aid the selection of the most appropriate drug candidates for further drug development.…”
Section: Resultsmentioning
confidence: 99%